2022
DOI: 10.1002/jex2.34
|View full text |Cite|
|
Sign up to set email alerts
|

The functional role of soluble proteins acquired by extracellular vesicles

Abstract: Extracellular vesicles (EVs) are lipid bilayer‐enclosed nanosized particles released by all cell types during physiological as well as pathophysiological processes to carry out diverse biological functions, including acting as sources of cellular dumping, signalosomes and mineralisation nanoreactors. The ability of EVs to perform specific biological functions is due to their biochemical machinery. Among the components of the EVs’ biochemical machinery, surface proteins are of critical functional significance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 152 publications
0
4
0
Order By: Relevance
“…[ 63 ] Though both miRNA and protein payloads can be differentially expressed in highly metastatic OS‐EVs, [ 64 ] our data suggests that this signal is transduced externally. This indicates membrane proteins, adsorbed nucleic acids, or other adsorbed molecules [ 65 ] may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…[ 63 ] Though both miRNA and protein payloads can be differentially expressed in highly metastatic OS‐EVs, [ 64 ] our data suggests that this signal is transduced externally. This indicates membrane proteins, adsorbed nucleic acids, or other adsorbed molecules [ 65 ] may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that non-vesicular components should not always be considered as contaminants. It has already been reported that the formation of a corona acquired from the extracellular milieu, composed by soluble proteins at the surface of extracellular vesicles can regulate and direct their function 65 . Proteoglycans, collagens, and non-collagenous proteins have been reported to be present in MVs preparations 66 , and the coexistence of MVs with these components within the extracellular matrix, has been long recognized at the ultrastructural level 67 .…”
Section: Discussionmentioning
confidence: 99%
“…-It is possible for EVs to acquire soluble proteins from the surrounding extracellular milieu (200)(201)(202).…”
Section: Communication With the Environmentmentioning
confidence: 99%
“…The main determinants are the physical and biochemical characteristics of their surface and protein concentration-based environmental changes. For example, during the pathogenesis of autoimmune diseases and innate and acquired immune responses, autoantigens may be packaged in EVs prior to or post-release (200)(201)(202).…”
Section: How Do Evs Communicate With Their Target Microenvironment?mentioning
confidence: 99%